The material politics of labour in Africa : A commentary - Ouma, Stefan (Territory, Politics, Governance, 2026)
In this commentary, I offer a sympathetic critique of the special issue, ‘Under Construction: Towards Critical Perspectives on Infrastructuring and Infrastructured Labour in Africa’. I highlight the importance of systems of provisioning, deeper theorising of the accumulation dynamics surrounding large-scale infrastructure projects, clearer distinctions between work and labour, and excavating the links between visible and hidden labour in various economic sectors, as key areas for future research that I hope will be inspired by this special issue.
Keywords: Labour; infrastructure; Political Economy; Politics; Africasystems of provisioning